Release of Formaldehyde from Endodontic Sealers - Sinan Evcil, M.; Kesmen, Zulal; Gurbuz, Taskin; Keles, Ali (Asian Journal of Chemistry, 2010)
Periapical alterations or irritations resulting from root canal therapy may be caused by over-instrumentation, infection or adverse effects from substances liberated from root canal filling materials. Chemotherapeutic agents containing formaldehyde are commonly used in the treatment of dental disease. Formaldehyde is known to local irritation and skin sensitization following acute and subacute exposure. The objective of this study was to evaluate AH 26, endomethasone, N2, AH plus, diaket, forfenan and roeko seal automix (RSA) for the presence of the formaldehyde. Sealer's powder and liquid were analyzed before and after mixing formaldehyde analysis was done using high-performance liquid chromatography with thermo-separation products spectra system and photodiode assay. Analysis showed that the AH 26, endomethasone, N2 powders and forfenan liquid contained formaldehyde and and their mixture were releasing formaldehyde. It could not decetcted any formaldehyde in AH plus, diaket and RSA samples. Because endodontic sealers can get into contact with surrounding soft and hard tissues, they should have an acceptable biocompatibility. Sealers with inferior biocompatibility, such as formaldehyde-releasing materials, should no longer be applicable in practice because safer alternatives are available.